Da Bears! : how the 1985 monsters of the midway became the greatest team in NFL history - Delsohn, Steve. frey50 (New York : Three Rivers Press, 2011)
A native Chicagoan tackles what many call the greatest team in NFL history, and tells the full story of the '85 legends-- with all the controversy and excitement-- on the field and off.
Up and then way down in '84 -- The '85 circus is open -- The Mike and Buddy show -- Jimmy Mac blows up in Minnesota -- Ditka's revenge gives birth to Fridge -- Payton saves the day -- Monster hits and bounties -- Bears have (too much) fun in Miami -- Shuffling to the playoffs -- Good times in the Big Easy -- Cakewalk in Super Bowl XX -- Did someone say dynasty?
Includes index.
Keywords: Chicago Bears (Football team) -- History; National Football League -- History